Combined Effects of Thermal Radiation and Magnetohydrodynamic on Peristaltic Flow of Nanofluids: Applications to Radiotherapy and Thermotherapy of Cancer - Hasona, Wahed; Almalki, Nawal; ElShekhipy, Abdelhafeez; Ibrahim, Mohamed (Current Nanoscience, 2020)
Background: Cancer is deadly to most of its patients. Consequently, researchers and modelers studies show that there are many ways to cure and destroy it. One of the effective ways is to inject the blood vessel close to the tumor with magnetic nanoparticles. Another way called the radiation therapy or radiotherapy, which eradicates cancer cells through high doses of radiation. Objective: This paper opts to investigate the influences of thermal radiation and variable electrical conductivity on peristaltic flow of Carreau Nanofluids. First order chemical reaction, Dufour and Soret effects are taken into consideration. Methods: The resulting system of partial differential equations is solved numerically with the aid of Parametric-NDSolve. Results for velocity, temperature and concentration distributions are obtained in the analytical two-dimensional and three-dimensional forms. The streamlines graphs are offered in the terminus, elucidating the trapping bolus phenomenon. Results: It has been found that thermal radiation is a decreasing function in the temperature of the fluid. As the temperature decreases, the diameter of the nanoparticles increases i.e., the volume of nanoparticle and its concentration increases and become more effective near tumor tissues. Conclusion: Radiotherapy and Thermotherapy are effective methods to cure and damage the tumor tissues.
Keywords: Thermal radiation